SUBYEK KEPEMIMPINAN TRANSFORMASIONAL PADA LEMBAGA PENDIDIKAN DASAR - Muhammad Arif Syihabuddin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2018)
This article discusses about transformational leadership. The main focus is the subject of transformational leadership in basic educational institutions. This study is important because the leaders in educational institutions are strategic positions to develop and make better changes. The method that used in this study is library research and then the data is interpreted with descriptive analysis, data is reduced, presented and verified, then concluded. The results of this study indicate that the main subject of transforma-tional leadership in basic educational institutions are headmasters. Headmasters or principals as leaders are become subjects who must transform through giving guidance or teachings to those who are led. Transformational leadership patterns can support the realization of system changes in basic education institutions, even able to bring changes in the quality of educational institutions to become more advanced and able to compete. Besides the headmaster or principal, the subject of transformational leadership in other basic educational institutions is the deputy head, teachers, parents and the community. These three elements must be able to synergize with the main subject of transformational leadership in the educational institution to achieve the goal.Keywords: Leadership, Transformational, Basic Education